Backing biodiversity? German consumers' views on a multi-level biodiversity-labeling scheme for beef from grazing-based production systems. (10th October 2022) - Stampa, Ekaterina; Zander, Katrin
Abstract: Biodiversity loss driven by intensive livestock farming constitutes a major threat to the resilience of food systems. Grazing-based beef production, by contrast, supports ecosystem services and biodiversity conservation. Communicating these benefits to consumers is vital to stimulate demand for pasture-raised beef, with labels being a key means of conveying such credence attributes. Despite extensive research on eco-labels and sustainability certification, however, we know little about consumer perceptions of labels designed to certify and highlight the biodiversity benefits of cattle products. To address this gap, we conducted six audio-only online focus group discussions with forty buyers of beef in Germany to explore consumer perceptions of a multi-level labeling system of labeling designed to differentiate between the conservation measures applied in pasture-raised beef production. Our findings indicate significant challenges for the implementation of such labeling, including low levels of understanding of biodiversity among consumers. Most participants struggled to discriminate between different levels of biodiversity conservation measures and placed little value on the biodiversity benefits of different products. Gaining trust in certification and control procedures is problematic due to the profusion of labeling schemes on the market, especially given consumers' time pressures. However, our findings also highlight consumers' appreciation for biodiversity conservation at local level and higher levels of trust in short supply chains, suggesting opportunities for selling pasture-raised beef at local level. The differences we identify in consumers' use of labeling can inform further segmentation research and targeted communications to market beef from grazing-based production systems.